REPRESENTASI BUDAYA MISTIS DALAM DIALOG FILM-FILM PENDEK KALIMANTAN SELATAN: KAJIAN ANTROPOLINGUISTIK (REPRESENTATION OF MYSTICAL CULTURE IN DIALOGUES OF SOUTH KALIMANTAN SHORT FILMS: AN ANTROPOLINGUISTIC STUDY) - Syahbana, Fitri (JURNAL BAHASA, SASTRA, DAN PEMBELAJARANNYA, 2024)
AbstractRepresentation of Mystical Culture in Dialogues of South Kalimantan Short Films: An Antropolinguistic Study. This research is intended to describe the form of objects, places, and times of mystical culture in the speeches of the characters in these short films and meaning of mystical culture in the dialogues of these short film. Anthopolinguistics was used in this research as a qualitative descriptive method. The data in this study are dialogues from figures relating to mystical culture of objects, places, and time. The data sources are document or archive data sources, in the form of 8 (eight) short films. The data collection technique was carried out by means of documentation using listening techniques, note-taking techniques, and data analysis techniques, namely content analysis techniques. Based on data analysis, it was found that there is a mystical culture related to objects, places, and times in the short film. The objects contained in the short film are offerings, tattoo (wafak), incense, mosquito nets, kuyang oil, perafen, and nyiru (rice winnowing). Places contained in the short film, rivers, forests, and rubber plantations. The time contained in the short film, namely night and dusk. Mystical culture related to objects, places, and time has been considered as a belief that has been believed for generations from generation to generation. Some people in South Kalimantan still believe in mystical culture. This happens because there is an inheritance from the family and the surrounding environment which makes this mystical culture still believed and implemented by some Banjar people.Keywords: representation, mystical culture, short film, antropolinguisticAbstrakRepresentasi Budaya Mistis dalam Dialog Film-Film Pendek Kalimantan Selatan: Kajian Antropolinguistik. Penelitian ini dimaksudkan untuk mendeskripsikan wujud benda, tempat, dan waktu budaya mistis pada tuturan para tokoh dalam film-film pendek dan makna budaya mistis dalam dialog film-film pendek. Antopolinguistik digunakan dalam studi ini dengan metode deskriptif kualitatif. Data pada penelitian ini adalah dialog dari tokoh yang berkenaan dengan budaya mistis terhadap benda, tempat, dan waktu. Sumber datanya, yaitu sumber data dokumen atau arsip, berupa 8 (delapan) film pendek. Teknik pengumpulan data dilakukan dengan studi dokumentasi yang menggunakan teknik simak, teknik catat, dan teknik analisis datanya yaitu teknik analisis konten (conten analysis). Berdasarkan analisis data, ditemukan budaya mistis yang berkaitan dengan benda, tempat, dan waktu dalam film pendek tersebut. Benda yang termuat dalam film pendek, yaitu sesaji, rajah (wafak), dupa, kelambu, minyak kuyang, perafen, dan nyiru (penampi beras). Tempat yang termuat dalam film pendek, yaitu sungai, hutan, dan kebun karet. Waktu yang termuat dalam film pendek, yaitu malam dan senja. Budaya mistis berkaitan dengan benda, tempat, dan waktu telah dianggap sebagai kepercayaan yang telah diyakini secara turun temurun setiap generasi. Hal tersebut terjadi karena adanya warisan dari keluarga dan lingkungan sekitar yang membuat budaya mistis tersebut masih dipercayai dan dilaksanakan oleh masyarakat Banjar.Kata-kata kunci: representasi, budaya mistis, film pendek, antropolinguistik